Mampukah Kepemilikan Institusional Mempengaruhi Tax Avoidance? - Vina, Vina; Trisnawati, Estralita; Firmansyah, Amrie (E-Jurnal Akuntansi; Vol 32 No 1 (2022)DO - 10.24843/EJA.2022.v32.i01.p10, 2022)
Taxes have a major contribution to state revenue. However, the tax for the company is a deduction from the profits earned. This study aims to empirically examine the effect of inventory intensity, fixed asset intensity, advertising expense on tax avoidance with institutional ownership as a moderating variable. This research was conducted in the primary consumer company sector listed on IDX in 2016 – 2019. The sample was selected using the purposive sampling method. The data analysis technique used Moderated Regression Analysis (MRA). The results showed that inventory intensity and fixed asset intensity had a positive effect on tax avoidance. Advertising expenses have a negative effect on tax avoidance. Institutional ownership cannot moderate the effect of inventory intensity and advertising expense on tax avoidance, but institutional ownership can strengthen the effect of fixed asset intensity on tax avoidance. Keywords : Inventory Intensity; Fixed Asset Intensity; Advertising Expense; Tax Avoidance; Institutional Ownership.